SIBLING PAIR ANALYSIS IN THE IDENTIFICATION PROCESS OF THE MADURESE POPULATION USING STR CODIS LOCI - Yudianto, Ahmad; Kurniawan, Arofi; Setiawan, Fery; Windrianatama Puspa, Egita; Youngest, Racy (African Journal of Infectious Diseases (AJID), 2022)
Background: The most common problem in forensic personal identification, particularly in paternity tests, is the availability of information originating from a mother or a father that can be used as a comparison in the forensic DNA examination process. The use of sibling analysis in paternity tests is still not widely known. Materials and methods: The respondents of this study were 25 families of the Madurese population with 6, 9, and 10 sibling pairs categorized as female-female, male-male, and male-female siblings. The kinship relationship was analyzed by using 13 STR CODIS loci technique (TPOX, D3S1358, FGA, D5S818, CSFIPO, D7S820, D8S1179, THOI, vWA, D13S317, D16S539, D18S51, D21S11), and Amelogenin (Amel) x: 106bp,y: 112bp). Results: The results of DNA contents and purity examination of the extracted DNA sample showed that the average value of DNA contents was 675±5.35 ng/μL with a purity range of 1.05-1.86. The findings proved that the male-male siblings of the Madurese population had the highest allele sharing percentage at the loci of D13S317, D16S539, and D21S11. The highest allele sharing percentage for female-female siblings was at the loci of TPOX and D21S11. Meanwhile, the male-female siblings had the highest allele sharing percentage at the loci of TPOX, D5S818, vWA, D7S820, THO1, vWA, and D13S317. Conclusion: The main STR loci recommended in the male-female siblings of Madurese population identification are TPOX, D13S317, and D21S11